Qualitative phytochemical screening of some selected medicinal desert species - Noshaba Dilbar; Sana Fatima; Majid Anwar; Zobia Anwer; Hina Ashraf (International Journal of Applied and Experimental Biology)
Desert plants are considered as a rich source of secondary metabolites and are used in drug development. The main objective of the current investigation was to explore the secondary metabolite profile of some desert plants and also compare the efficiency of different solvents. Plants [Psidium guajava L., Thuja orientalis L., Callistemon citrinus (Curtis) Skeels, Capparis spinosa L. and Dipterygium glaucum Decne.] were collected from the Cholistan desert of Bahawalpur based on the traditional knowledge. Five types of extracts (petroleum ether extract, benzene extract, chloroform extract, ethanol extract and methanol extract) were prepared for both fresh and dry plant materials. The methanol extract showed the highest efficiency to detect the secondary metabolites as compared to that of all other extracts. Qualitative phytochemical analysis of these plants confirmed the presence of various important secondary metabolites, viz. phlobatannins, alkaloids, steroids, glycosides, flavonoids, terpenoids, quinones, anthocyanins, saponins, phenols, phytosterols and tannins in different parts (leaf, fruit, seed and whole plant). These results clearly show that potential bioactive compounds can be effectively extracted from important medicinal plants which could be potentially utilized by pharmaceutical industries.